The Quest for Improving Treatment of Cancer of Unknown Primary (CUP) Through Molecularly-Driven Treatments: A Systematic Review - Lombardo, Roberta; Tosi, Federica; Nocerino, Annunziata; Bencardino, Katia; Gambi, Valentina; Ricotta, Riccardo; Spina, Francesco; Siena, Salvatore; Sartore-Bianchi, Andrea (Frontiers in Oncology, 2020)
Background: Carcinomas of unknown primary (CUP) account for 3%-5% of all malignancy and, despite a reduction in incidence, the overall survival has not improved over the last decade. Chemotherapy regimens have not provided encouraging results. New diagnostic technologies, such as next generation sequencing (NGS), could represent a chance to identify potentially targetable genomic alterations in order to personalize treatment of CUP and provide insights into tumor biology. Methods: A systematic review of studies of patients with CUP, whose tumor specimen was evaluated through a NGS panel, has been performed on June 10th , 2019 according to PRISMA criteria from PubMed, ASCO meeting library and Clinicaltrial.gov. We have identified potentially targetable alterations for which approved/off-label/in clinical trials drugs are available. Moreover, we have included case reports about CUP patients treated with targeted therapies driven by NGS results in order to explore the clinical role of NGS in this setting. Results: We have evaluated 15 publications of which eleven studies (9 full-text articles and 2 abstracts) have analyzed the genomic profiling of CUPs through NGS technology, with different platforms and with different patients cohorts, ranging from 16 to 1,806 patients. Among all these studies, 85% of patients demonstrated at least one molecular alteration, the most frequent involving TP53 (41.88%), KRAS (18.81%), CDKN2A (8.8%), and PIK3CA (9.3%). A mean of 47.3% of patients harbored a potentially targetable alteration for which approved/off-label/in clinical trials drugs were available. Furthermore, we have identified 4 case reports in order to evaluate the clinical relevance of a specific targeted therapy identified through NGS. Conclusions: NGS may represent a chance to improve diagnosis and treatment of CUP by identifying actionable alterations and providing insights into tumor biology.